TAXONOMIC STUDY OF PANDANUS (PANDANACEAE) IN SWAMP AREA, ACEH SINGKIL - Dwi Ratna Anjaning Kusuma Marpaung; Nursahara Pasaribu; Alief Aththorick (Jurnal Natural, 2013)
Taxonomic study on Pandanus (Pandanaceae) in swamp area, Singkil had been conducted from November 2012 until June 2013. Based on morphological characters,  5 species of Pandanus have been identified in the area  as  Pandanus atrocarpus, Pandanus labyrinthicus, Pandanus militaris, Pandanus odoratissimus and Pandanus tectorius. The morphology and life cycle of species were categorized into two types, and they are medium arborescent pandan  (Pandanus labyrinthicus and Pandanus militaris) and large arborescent pandan (Pandanus atrocarpus, Pandanus odoratissimus and Pandanus tectorius).  Anatomical characters of Pandanus such as stomata (type, size, papilla) and epidermal cells supported the morphological features.